The Development of Instant Juice Powder from Half-Ripe Carissa carandas L. by Spray Dryer and the Study on Physicochemical and Functional Properties - Srimongkoluk, Ubolwanna; Lekhavat, Supaporn (Journal of Food Technology, Siam University, 2023)
The development of instant juice powder product from half-ripe Karonda (Carissa carandas L.) extract using spray drying technique had been performed. Maltodextrin in feed solution in drying were varied at 20, 25, and 30% wt. of feed solution, respectively. Instant beverages formular were developed by using sugar substitutes such as sucralose, stevioside and erythritol. Relative sweetness of each recipe to sucrose were controlled at 5, 7 and 9% of sucrose, respectively. After that sensory quality of instant beverages were evaluated. The results showed that soluble solids of juice extracts from ripe and half-ripe Karonda are in range of 22.77+0.06 and 23.10+0.10 °Brix. Both extracts had pH value of 4.0. Phenolic compounds of juice extracts from ripe and half-ripe Karonda are in range of 6.90+1.63 and 23.32+0.96 mg.GAE/ml., respectively. The IC50 value of half-ripe fruit was 3.81±0.73 mg/ml, while that of ripe fruit had a higher IC50 value of 7.30 ± 0.38 mg/ml. However, it was not found any statistically significant of phenolic content (4.48-5.44 mg.GAE/ml), IC50 values (2.88-4.03 mg/ml), and HMG-CoA reductase enzyme inhibition values (1.11-1.19 unit/mg. protein) in spray dried half-ripe Karonda extract with three levels of maltodextrin. In addition, spray dried half-ripe Karonda extract at concentration of 5,000 g/ml could inhibit the activity of HMG-CoA reductase enzyme by 35-38% compared to pravastatin at concentration of 0.5 g/ml. From sensory evaluation results, it was showed that an instant powder recipe containing 30% of maltodextrin consisting of 0.004 % sucralose and 0.075% stevioside that had relative sweetness to 9% sucrose obtained consumer acceptance higher than 90%.